Sistem keamanan folder dengan menggunakan algoritma rivest code 4: Sistem keamanan folder dengan menggunakan algoritma rivest code 4 - Shania Oktawijaya; Ilka Zufria; Abdul Halim Hasugian (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
Article history: The use of technology is an important need for society, so that data security is also increasingly stretched by crimes in the form of destruction or theft of data by irresponsible people. Securing the contents of data in a folder, for example, will keep the data safe and confidential so that it cannot be seen by anyone other than the intended recipient. Therefore, one way of storing data in folders must be treated in a special way, namely by using cryptography. Cryptography is the science and art of protecting the confidentiality of communications involving data and information. The Rivest Code 4 algorithm, a cryptographic technique, uses binary operations (XOR) to combine plaintext with stream ciphers that use the same key for bitwise or byte-by-byte encryption, so that security is maintained.